Tecnologia assistiva na distrofia muscular de Duchenne: aporte para deambulação e atividades de vida diária - SILVA, Vinícius Costa da (2021)
Duchenne muscular d/stroph/ (DMD), incapacitating pathology and second most frequent genetic disorder in humans. Assistive Technology {T.A) is a resource for treating and promoting the independence of this public. Objective: To review publications related to the use of T.A in DMD and their contributions to arnbulation and da’if[ activities. Methodology: they are based on a systematic literature review based on PUBMED, PEDRO, SCIELO and BVS databases. Results: 219 articles were found, of vrbicb 4 were selected because they related to the theme. Conclusion: Importance of the study for T.A area aimed at identiJing the functions that it has in the treatment of DMD.